Survival and re-aerosolization in dust of mycobacterium smegmatis - a surrogate for mycobacterium tuberculosis - Tshilombo, Kazadi Valéry (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)-- Stellenbosch University, 2017.